Information and communication technologies in parliamentary libraries - Bedmund Balnaves (2012)
The Handbook provides parliamentary staff- in senior managerial position of library and IT staff - with an overview of guidance on ICT tools and systems that parliamentary libraries can adopt and implement in different ways. These tools and systems should help libraries to perform their mandate more effectively and deliver more efficient services